Pengaruh Laba, Ukuran Perusahaan dan Efisiensi Perusahaan terhadap Harga Saham pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2024 - Betris Monika; Rahmi Isriani (Lembaga Yasin AlSys, 2026)
Although stock prices are theoretically influenced by fundamental factors that reflect company performance, in the consumer goods industry there are still conditions in which improvements in fundamental performance are not followed by increases in stock prices. Studies that specifically discuss the effect of earnings, company size, and company efficiency on stock prices during the 2020–2024 period also remain limited. This study aims to analyze the magnitude of the effect of earnings, company size, and company efficiency on stock prices in consumer goods industry companies during 2020–2024. This study employed a quantitative approach with an associative design. The data used were secondary data from company financial statements obtained through the official website of Bursa Efek Indonesia for the 2020–2024 period. The research sample consisted of 16 companies selected using purposive sampling. The data were analyzed using the EViews application through the panel data regression method. The results showed that earnings proxied by EBITDA had a positive and significant effect on stock prices, with a t-value of 2.301873 ≥ the t-table value of 1.991673 and a probability value of 0.0241 ≤ 0.05. In contrast, company size proxied by Ln Assets and company efficiency proxied by TATO had no significant effect on stock prices, with probability values of 0.9151 and 0.3905, respectively. Simultaneously, earnings, company size, and company efficiency also had no effect on stock prices, with a probability value of 0.104355 ≥ 0.05. These findings contribute to the development of financial theory by confirming that earnings are a more dominant indicator in determining stock prices, while also providing practical implications for investors in making investment decisions.